2015
DOI: 10.1177/0011000015608949
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Psychology

Abstract: Given the increasing number of women entering the field of psychology, this study investigated the degree to which achievement motivation, leader identity, career salience, and willingness to compromise career for partner and children were predictive of leadership aspirations generally and in the American Psychological Association. Data from 202 female graduate students in counseling and clinical doctoral programs indicated that leader identity, career salience, and willingness to compromise career for childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
(46 reference statements)
1
19
1
1
Order By: Relevance
“…Respondents express agreement with each item on a scale ranging from 1 (Strongly disagree) to 5 (Strongly agree). Further, a modification of the Leadership Aspiration Subscale (LAS; Gregor & O'Brien, 2015) was also employed, to measure perceptions of males toward female leadership aspirations. This questionnaire consisted of six items on the men's perceptions of women's leadership aspirations.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents express agreement with each item on a scale ranging from 1 (Strongly disagree) to 5 (Strongly agree). Further, a modification of the Leadership Aspiration Subscale (LAS; Gregor & O'Brien, 2015) was also employed, to measure perceptions of males toward female leadership aspirations. This questionnaire consisted of six items on the men's perceptions of women's leadership aspirations.…”
Section: Methodsmentioning
confidence: 99%
“…For example, women doctoral students, and women in academia in general, balance contradictory and multiple roles throughout their programs, including a multitude of gendered negotiations relative to family and other relationships. Gregor (2015) described the how gendered norms and sexism directly tied women's opportunities for academic leadership to the degrees to which they chose career over family. Their study found that greater emphasis on family equated to limited professional promotions and vice versa (see also Bireda, 2015;Holm, Prosek,…”
Section: (Wo)monstrous Ethical Responsibility and Vulnerabilitymentioning
confidence: 99%
“…l doctorado permite obtener un conocimiento avanzado, desarrollar funciones de liderazgo y realizar investigaciones (Gregor & O'Brien, 2015;Hoyne, Alessandrini, & Fellman, 2016). En los últimos años, el doctorado ha evolucionado acorde con las nuevas demandas que se imponen sobre los mismos (Melin & Janson, 2006), las cuales requieren la enseñanza de nuevas habilidades y competencias.…”
unclassified